2013
DOI: 10.1007/s10853-013-7717-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal expansion coefficient and thermal fatigue of discontinuous carbon fiber-reinforced copper and aluminum matrix composites without interfacial chemical bond

Abstract: International audienceFully dense carbon fiber-reinforced copper and aluminum matrix (Cu-CF and Al-CF) composites were fabricated by hot press without the need for an interfacial chemical compound. With 30 vol% carbon fiber, the thermal expansion coefficients (TECs) of pure Cu and Al were decreased to 13.5 × 10−6 and 15.5 × 10−6/K, respectively. These improved TECs of Cu-CF and Al-CF composites were maintained after 16 thermal cycles; moreover, the TEC of the 30 vol% Cu-CF composite was stable after 2500 therm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…The outcome of this principle is that the protection to plastic deformation and work hardening capacity increase in the composites [39]. The indirect strengthening arises in the composites from the thermal mismatch due to uneven cooling between matrix alloy, which has a higher coefficient of thermal expansion (CTE) and ceramic particles with lower CTE [40]. The development of dislocations at the interface between matrix and reinforcement particle occur with a thermal mismatch, a result that is increased in dislocation density that contributes to improving the strength of the composites [37].…”
Section: Ultimate Tensile and Yield Strengthmentioning
confidence: 99%
“…The outcome of this principle is that the protection to plastic deformation and work hardening capacity increase in the composites [39]. The indirect strengthening arises in the composites from the thermal mismatch due to uneven cooling between matrix alloy, which has a higher coefficient of thermal expansion (CTE) and ceramic particles with lower CTE [40]. The development of dislocations at the interface between matrix and reinforcement particle occur with a thermal mismatch, a result that is increased in dislocation density that contributes to improving the strength of the composites [37].…”
Section: Ultimate Tensile and Yield Strengthmentioning
confidence: 99%
“…However, the gaps at the Al particle boundaries created by the existence of the MWCNTs were filled up with Al. It has been reported that and the thin Al 2 O 3 layer on Al particle can be fractured by the surface cleaning effect in SPS [17][18][19][20]. Therefore, it seems that Al has transformed to liquid phase in SPS, and infiltrated into the gap through the fractured Al 2 O 3 layer as can be seen by the white broken arrows in Figure 1b.…”
Section: Methodsmentioning
confidence: 88%
“…Currently, in the automotive and aeronautical industries, thermomechanical properties have acquired great importance due to the different components used in these systems. In this sense, composites based on graphene, carbon fiber, fiberglass, and natural fibers have explored new applications in these two areas ranging from the manufacture of parts that constitute the external or internal structure of automobiles and aircraft and the electronic application that helps to protect and, at the same time, dissipate the heat [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the thermal properties of the composites formed by carbon fiber, glass fiber, and natural henequen fiber reinforced with a polymer matrix, aluminum, and alumina (Al 2 O 3 ) have been investigated. Under this context, studies showed that the addition of aluminum [25,50] and alumina particles in carbon fiber-based composites changes the thermomechanical properties [4]. On the contrary, the sheets used were carbon fiber (CF), glass fiber (GF), and natural henequen fiber (NHF), as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%